The Employment At-Will Doctrine: Second Level Ethical Issues and Analysis - Roehling, Mark V. (Journal of business ethics, 2003)
There is an ongoing debate over the ethical status of policies that give an employer the right to discharge an employee without a good reason or notice (i.e., employment at-will policies). This article moves beyond the question of whether the adoption of such a policy is unethical per se under all circumstances, focusing instead on the following question: Assuming that an at-will policy is not unethical per se in all circumstances, what are the ethical issues associated with an employer's implementation and maintenance of an employment at-will policy, and how can these issues be addressed? Three primary ethical concerns are identified and discussed, and specific propositions regarding employers' obligations are presented. The article concludes by offering practical guidance intended to assist at-will employers in meeting the identified ethical obligations.